RISK FACTOR FOR GOUT AND PREVENTION : A SYSTEMATIC REVIEW - Rossiyah, Nella (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Due to the supersaturation of uric acid, monosodium urate monohydrate crystals accumulate in the tissues, causing gout. Gout is characterized by elevated serum urate levels, acute gouty arthritic episodes, the production of tophi, gouty nephropathy, and uric acid stones. Until now there is no definite percentage/number of people with gout arthritis in the world, due to differences in research sampling methods in determining the number of sufferers of this disease. However, especially in America, there has been a significant increase in cases of gouty arthritis in the last 10 years. Uric acid is a waste product created by the body when renewing cells of gout patients produce more uric acid in the body and the body is unable to eliminate uric acid through urine, causing uric acid to accumulate in the blood. Significant roles are played by genetics, gender, and diet (alcohol intake, obesity) in the development of gout. The underlying cause of hyperuricemia determines the elements that lead to the development of gout. A diet heavy in purines can precipitate gout episodes in individuals with congenital defects in purine metabolism that result in elevated uric acid generation. Many risk factors for gout have been identified via research, including alcohol risk behavior (only in males), body mass index, estimated glomerular filtration rate, triglycerides, and triglyceride levels. Gout sufferers should avoid uric acid-raising meals and beverages. The patient drinks plenty of water. Gout sufferers should exercise regularly. To maintain weight, walk 150 minutes per week or 30 minutes each day. Avoid uric acid-raising medications like hydrochlorothiazide, aspirin, and cyclosporine.